Utilization of the light density to reduce the development of Lyngbya sp. and their growth on Caulerpa lentillifera J. Agardh in a recirculating aquature system - Quemper, Florian; Dam, Tien Duc; Nguyen, Linh Manh; Nguyen, Anh Thi Mai; Nguyen, Hoang; Vu, Hung Manh (Vietnam Journal of Marine Science and Technology, 2020)
The release of pollutants is endangering ecosystems, biodiversity and seafood. Therefore, it is of the requirement to create innovative methods in seafood production. Caulerpa lentillifera J. Agardh is a well-known seaweed for its properties and edible. We cultured C. lentillifera in a recirculating aquaculture system under laboratory conditions. However, after 7 days the culture was invaded by epiphyte algae Lyngbya sp. This experiment was designed to remove those algae by using light density as a treatment. Two irradiances were tested including 20 μmol photons m-2.s-1 (low light density) and 40 μmol photons m-2.s-1 (initial light density). Every week we measured the stolon length, thallus weight, and calculated the specific growth rate. Results showed that after 30 days C. lentillifera under low light density regained their healthy green color and Lyngbya sp. was no longer present. Meanwhile, in the initial light density (40 μmol photons m-2.s-1) Lyngbya sp. covered almost all thalli of C. lentillifera, and half of them were dead. The measured results of specific growth rate (%d-1) and weight (g) of C. lentillifera in low light density conditions were better than those of C. lentillifera in the initial condition. The light density, therefore, might be used as a treatment to remove Lyngbya sp. from Caulerpa lentillifera in aquaculture.